Multiplexing of fiber-optic long-period grating-based interferometric sensors - Murphy, Richard P.; James, Stephen W.; Tatam, Ralph P. (Institute of Electrical and Electronics Engineers (IEEE), 2007)
Two long-period gratings (LPGs) fabricated in series in an optical fiber form a Mach-Zehnder interferometer, producing a sinusoidal channelled spectrum within the characteristic LPG attenuation bands, which has the appearance of an interference fringe pattern. The phase of the fringes is sensitive to changes in the surrounding environmental parameters, such as refractive index. Fabrication of a number of identical cascaded LPG pairs with different separations produces independent fringe patterns of different frequencies within the attenuation bands. The application of basic Fourier techniques to analyze the transmission spectrum allows the phase of each fringe pattern to be determined independently, facilitating the differentiation of external effects acting on each interferometer